Potential role of mushroom beta-glucans in immunity and inflammation in viral infections and COVID-19 - Valentina Konusova; Eugene Vorbeychikov; Mark Shamtsyan (Journal of Food Bioactives, 2021)
According to the concept of trained immunity (TRIM), by stimulating the immune response with one pathogen, one can strengthen it against infection by another. With this understanding, one can take advantage of such immune responses with a stimulant such as β-glucan, which does not actually cause disease in humans, but has the advantage of generating primed immune cells that will respond to a variety of deadly infections. Mushroom β-glucans are known to act as training agents that leads to an increase in immune responses when these trained cells are subjected to a secondary stimulus. Understanding whether the TRIM processes are responsible for antiviral responses will undoubtedly provide a deeper understanding of other potential antiviral strategies, as the new SARS-CoV-2 is not the first- or last-time humanity has to deal with viral pandemics. More studies and clinical evidence are necessary for better understanding of the role of β-glucans in viral infections and COVID-19.